Success Stories of Top Performers in Teacher Education and Liberal Arts - Manuel, Kyla; Diaz, Tricia Mae; Burigsay, Frances Anne; Bangi, Jennifer; Luyun, Cecille (Journal of Interdisciplinary Perspectives, 2024)
This study was conducted to describe the journey of topnotchers from a private Catholic higher education institution in Tuguegarao City. Employing a phenomenological study approach, this study explored the lived experiences of the four topnotchers from the School of Education, Criminology, Arts, and Psychology between 2013 and 2023. Using thematic analysis to analyze the answers of the top notchers to the validated semi-structured interview questionnaire, several key factors that contributed to their success in achieving top placements in the board examinations were revealed. These factors were strong institutional support, effective teacher mentorship, good personal characteristics, a supportive family, peer support, and strategic personal interventions. These emphasize how important it is to have a solid support system inside and outside the school setting. Based on these results, the study offers various recommendations for the institution to enhance further its support for those students who are determined to succeed. These include strengthening academic and emotional support strategies from the school, family members, and peers. Moreover, it is important to invest in faculty development, enrich library resources, and intensify board exam review courses to incorporate meaningful learning experiences and test the effectiveness of a certain practice. Additionally, assessing students’ study routines to improve effective study habits and leveraging more top-notch testimonies for promotional purposes to attract more enrollees. These could serve as a source of inspiration for students and a means of enhancing the school’s standing as a producer of high scorers on board exams. Therefore, this study encourages students to pass and ace the board examinations.